The Impact of attractions, amenities and ancillaries on visitor satisfaction at traditional culinary service providers in the city of Palembanig - Isti Apriliani; Dendy Ardana; Rini (Department of Business Administration Politeknik Negeri Sriwijaya, 2025)
This traditional culinary service provider is one of the oldest culinary tours in the city of Palembang and has its own characteristics and charm. The tourist attraction used as the location for this research is a provider of traditional culinary services. The aim of this research is none other than to determine the influence of attractions, amenities and ancillaries on visitor satisfaction. This type of research also uses quantitative methods, and the sample used was 99 respondents with sampling using nonprobability sampling. Data collection techniques are carried out in two ways, namely questionnaires and literature study. The results of the research that has been carried out show that attractions, amenities and ancillaries have a positive and significant effect on partial visitor satisfaction. These results were obtained from data analysis using validity tests, reliability tests, multiple linear regression analysis, coefficient of determination and t tests and F tests.